Some Developments in Aristotle's Conception of Magnanimity - Irwin, Terence (Pontificia Universidad Católica del Perú. Fondo Editorial, 1999)
El tratamiento de la magnanimidad en las tres obras éticas de Aristóteles nos da una oportunidad de comparar sus diferentes discusiones y sus diferentes tratamientos de las concepciones del sentido común así como diversos ideales de magnanimidad. Una comparación de las tres éticas sugiere que la Ética a Nicómaco provee el mejor y más duradero tratamiento de la virtud.

The treatment of magnanimity in Aristotle's three ethical works gives us an opportunity to compare his different discussions, and his different treatments of common-sense views and various ideals of magnanimity. Comparison of the three Ethics suggests that the Nichomaechean Ethics provides the latest and best treatment of this virtue.
Some Developments in Aristotle's Conception of Magnanimity
Keywords: Filosofía; https://purl.org/pe-repo/ocde/ford#6.03.01